2018
DOI: 10.1007/s00383-018-4316-3
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Alagille syndrome following the Kasai operation: a systematic review and meta-analysis

Abstract: The Kasai operation was associated with poor outcomes in AGS patients. It remains unclear if the Kasai operation directly deteriorates liver and patient outcomes in AGS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Intraoperative cholangiography (which can be undertaken laparoscopically) was considered a definitive and gold standard for diagnosing BA until the twenty-first century ( 7 9 ). This technique, however, from the beginning has been reported to lead to misdiagnoses in 1967 ( 10 ), and this situation is now revealed by an increasing number of studies ( 11 17 ). Furthermore, the Cholestasis Guideline Committee stated that intraoperative cholangiography could be misleading in up to 20% of the cases ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intraoperative cholangiography (which can be undertaken laparoscopically) was considered a definitive and gold standard for diagnosing BA until the twenty-first century ( 7 9 ). This technique, however, from the beginning has been reported to lead to misdiagnoses in 1967 ( 10 ), and this situation is now revealed by an increasing number of studies ( 11 17 ). Furthermore, the Cholestasis Guideline Committee stated that intraoperative cholangiography could be misleading in up to 20% of the cases ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fujishiro et al carried out a systematic review [6 studies (394 AGS patients)] and found that liver transplantation (odds ratio:6.46) and mortality (odds ratio:15.05) were significantly higher in AGS patients who underwent a Kasai than in those who did not. (2) An intra-operative cholangiogram may help in solving this diagnostic dilemma however in AGS there may be non-visualisation of the common hepatic duct or confluence masquerading as BA. (4) Eventually it is testing for JAG1 (or rarely NOTCH2) mutation that gives one a confirmatory diagnosis as seen in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…(1) There have been reports in the past where children with AGS have been initially diagnosed as BA and have even inadvertently undergone a Kasai procedure, which has led to poor outcomes. (2) We present a 2.5-month old female in whom the diagnostic dilemma between AGS and BA was eventually sorted by genetic analysis. We highlight the clinical, biochemical and radiological features that helps one in differentiating between these two conditions.…”
Section: Introductionmentioning
confidence: 99%
“…16 In addition, a recent systematic review indicated that patients who underwent KP could have a poor prognosis. 17 Therefore, the possibility of other BA cases of subgroup ο overlapping Alagille syndrome in the JBAR cannot be excluded. Therefore, BA with subgroup ο should be managed with careful attention to the association with Alagille syndrome.…”
Section: Discussionmentioning
confidence: 99%